Canada and ocean climate adaptation: tracking law and policy responses, charting future directions - David L. VanderZwaag; Sara L. Seck; Laura Graham; Jonathon Frontain; Kieran Simpson (Frontiers in Marine Science, 2023)
This research article provides a law and policy summary of climate change adaptation initiatives in Canada at the ocean-climate nexus. Three levels of governance are examined (national, provincial, and Indigenous) with a focus on the Atlantic region. The research method was the review of relevant and newly amended laws, regulations and policy statements, and related commentaries. The roles of the federal government are first described with key developments including the launch of a Climate Adaptation Platform in 2012 to share adaptation experiences and information and release of a National Adaptation Strategy and accompanying Adaptation Action Plan in November 2022. Federal adaptation efforts in the areas of fisheries, aquaculture and shipping are also reviewed along with progress in establishing marine protected areas (MPAs) and other effective area-based conservation measures. Provincial adaptation initiatives are next summarized with a focus on the four Atlantic provinces. Those provinces have established a regional hub, CLIMAtlantic, to provide climate information and advance climate-related research and training. Each province has developed a climate action plan which includes climate adaptation priorities. Indigenous-led climate engagement and adaptation initiatives are finally described including the publication in 2019 of a National Inuit Climate Change Strategy , regional initiatives of the Atlantic Policy Congress of First Nations Chiefs Secretariat, and the development of climate adaptation plans by select First Nation communities in the Atlantic region. The paper concludes by discussing future law and policy directions to make Canada more “climate ready.” Adoption of climate adaptation strategies for governmental departments and agencies with ocean and coastal responsibilities should be a priority. Incorporating climate change adaptation responsibilities through legislative and regulatory changes also needs to be considered, for example, by amending Canada’s Oceans Act to recognize the role of oceans in climate adaptations and mitigation, to authorize the designation of MPAs as climate refuges and to require adaptive and dynamic MPA management plans through strict monitoring and timely review provisions. Indigenous peoples must be effectively included in all climate adaptation discussions and planning.